Pengaruh Promosi Penjualan dan Kualitas Distribusi Terhadap Perputaran Persediaan di PT Teman Hebat Indonesia Kota Bandung - Rivaldy Al Faruqi; Halimah Zahrah; Indra Sasangka (Indo Publishing, 2026)
This quantitative study analyzes the impact of Sales Promotion and Distribution Quality on Inventory Turnover at PT Teman Hebat Indonesia, addressing the issues of slow-moving items and stock fluctuations. Based on multiple linear regression analysis using SPSS 25, the results show that both Sales Promotion (t_count 4.164) and Distribution Quality (t_count 4.196) have a significant positive impact on inventory turnover. Simultaneously, both variables significantly influence the dependent variable with an F-value of 38.452. The Coefficient of Determination (R^2) is 56.2%, indicating that while these factors are crucial for optimizing goods flow and reducing overstock, the remaining 43.8% is influenced by external variables.